Libro de trabajo en lengua y literatura para los niños y niñas de 2do y 3ero de la educación básica del centro educativo intercultural bilingüe “atahualpa”, de la comunidad chaupiloma, parroquia tupigachi, cantón pedro moncayo; de acuerdo a la actualización y fortalecimiento curricular de la educación general básica. - Bautista Calagullín, María Celinda (2014)
Teaching Language and Literature in second and third level of basic general education is essential, because it is the basis for the development of macro skills such as listening, speaking, reading and writing. The development of orality in the first levels to communicate with ease; especially raises the self-children and girls, increases the degree of confidence in themselves and in others. Learning the language and literature in children and indigenous girls greatly help to correct various errors in the pronunciation of the words used in everyday communication in any social field and in the writing of sentences, sentences and texts. Methodological strategies Language Arts will facilitate the development of critical thinking and logical reasoning.